ChemInform Abstract: Copper‐Catalyzed Hydrodefluorination of Fluoroarenes by Copper Hydride Intermediates. Issue 30 (4th July 2013) - Lv, Hongbin; Cai, Yuan‐Bo; Zhang, Jun‐Long
Abstract A variety of fluorobenzenes and pentafluoropyridine are subjected to the methodology.